Model symulacyjny rozproszonego systemu pomiarowo - sterującego - Markowski, Adam
The basic aim of a work was investigation of a relations between delays in data transmission in DMCS, looking for a causes and place their appearing and influence of a delays on the DMCS. functioning. A lot diversity of a situations in which delays are present, a complexity of the analytical description this kind of relations and requirement of a knowledge of a quantity and kind of delays on the design stage determine range, importance and way of conducting researches. Aims have been achieved by means of DMCS simulation model developed by author. This approach is very useful because results getting from simulation can be helpful for DMCS designer. Worked-out simulator was verified by use of a analytical and experimental approaches. Achieved simulation results can be useful to choose suitable system or node structures and can indicate if tasks deadlines executed by node processor and communication tasks deadlines are meet.
Keywords: rozproszony system pomiarowo - sterujący; symulacja zdarzeń dyskretnych; system czasu rzeczywistego; analiza czasowa